Plasma and magnetic field dynamics in POS: pic simulations - Manuilenko, O.V.; Onishchenko, I.N.; Pashchenko, A.V.; Pashchenko, I.A.; Yuferov, V.B. (Problems of Atomic Science and Technology, 2022)
2D3V particle in cell computer simulations for plasma, magnetic field and current density spatio-temporal dynamics in plasma opening switch (POS) are presented for various initial plasma densities. The current channel formation in the POS’s plasma, its passage through the plasma bridge, and its destruction at the boundary of the plasma jumper are studied. It is shown, that during the penetration of the magnetic field into the POS’s plasma and current channel formation, electron vortices are excited. The passage speed of the POS’s plasma by vortices decreases with increasing plasma density, which is qualitatively consistent with estimates based on classical electron magnetohydrodynamics (EMHD).